Les élastomères silicones - A. Richard (CHIMIA)
The first silicone rubber was made in 1945. Now there are two types of silicone rubbers : heat vulcanizing silicone rubbers and room temperature vulcanizing silicone rubbers. They have in common many properties but they are quite different in their nature and uses.